Photoshop elements 4 solutions : the art of digital photography - Aaland, Mikkel, 1952- (Wiley, 2005)
Now updated to cover the latest program version, this is the ultimate full-color guide for Photoshop Elements users want to get the most out of the programThis new edition features a tighter organization and new and enhanced content based on reader feedbackPractical solutions, stunning full-color images, and a reader-friendly design take readers to a new level of image-editing expertiseNow bargain-priced at under 30-10 less than the previous edition!